Pengaruh Tingkat Pengangguran dan Tingkat Kemiskinan Di Provinsi Nusa Tenggara Timur Tahun 2019-2023 - Magnus Alansius Bebo; Joko Priyono (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study was to determine the effect of Unemployment Level and Education on Poverty Level in East Nusa Tenggara Province in 2019-2023. The data analysis technique used in the study is the quantitative method. The data processing technique in this study uses the assistance of the SPSS (statistical package for the social sciences) software program. The data analysis technique in this study is multiple linear regression analysis, hypothesis testing and analysis of the coefficient of determination (R2). In this study, the type of data used is quantitative and uses secondary data sources. The results of this study indicate that the Unemployment Level and Education simultaneously affect Poverty in East Nusa Tenggara Province. Meanwhile, based on the results of the t-test, the Unemployment variable has a significant positive effect on Poverty in East Nusa Tenggara Province, Education has a positive and significant effect on Poverty in East Nusa Tenggara Province